G-band (140-220-GHz) InP-based HBT amplifiers. - Urteaga, M. (IEEE Journal of solid state circuits)
We report tuned amplifiers designed for the 140-220-GHz frequency band. The amplifiers were designed in a transferred-substrate InP-based heterojunction bipolar transistor technology that enables efficient scaling of the parasitic collector-base junction capacitance. A single-stage amplifier exhibited 6.3-dB small-signal gain at 175 GHz. Three-stage amplifiers were subsequently fabricated with one design demonstrating 12.0-dB gain at 170 GHz and a second design exhibiting 8.5-dB gain at 195 GHz.